2011
DOI: 10.1002/aenm.201100274
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Monodisperse Single‐Walled Carbon Nanotube Thin Films as Transparent Conducting Anodes in Organic Photovoltaic Devices

Abstract: Due to the high cost, brittle nature, and suboptimal electronic and chemical properties of indium tin oxide (ITO), [ 1 − 4 ] alternative transparent conducting anode materials have played an increasingly important role in organic photovoltaic (OPV) device research. For example, thin fi lms of single-walled carbon nanotubes (SWNTs) have been identifi ed as a promising option due to their excellent electronic properties, solution processability, elemental abundance, environmental stability, and robust mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 43 publications
1
85
0
Order By: Relevance
“…Contact angle measurements have shown that the PEDOT:PSS solution has a better wettability with the PANI:CNT electrode than with ITO (as can be seen in Figure S4, Despite the great advantages of the PANI:CNT fi lms, their properties do not seem to affect other device characteristics. The fi ll factors (FF), [ 41 ] which are ultimately related to the series resistance of the device (limited in these cases by the anode), are very similar for devices built using ITO, FTO, and PANI:CNT. The V OC value of the PANI:CNT device is also very similar to that observed for ITO device.…”
Section: Photovoltaic Devices Using Pani:cnt Electrodesmentioning
confidence: 98%
“…Contact angle measurements have shown that the PEDOT:PSS solution has a better wettability with the PANI:CNT electrode than with ITO (as can be seen in Figure S4, Despite the great advantages of the PANI:CNT fi lms, their properties do not seem to affect other device characteristics. The fi ll factors (FF), [ 41 ] which are ultimately related to the series resistance of the device (limited in these cases by the anode), are very similar for devices built using ITO, FTO, and PANI:CNT. The V OC value of the PANI:CNT device is also very similar to that observed for ITO device.…”
Section: Photovoltaic Devices Using Pani:cnt Electrodesmentioning
confidence: 98%
“…373 Since nitric acid treated semiconducting SWCNTs exhibit lower sheet resistance than comparably treated metallic SWCNTs, 382,383 the dramatically reduced PCE for semiconducting SWCNTs appears counterintuitive. However, it was shown that the films were dedoped by the hole transport layer PEDOT:PSS in the fabricated OPVs, 381 thus compromising the sheet resistance of the semiconducting SWCNTs to a much greater degree than the metallic SWCNTs. Further improvements in sheet resistance and thus OPV power conversion efficiency can be achieved with longer CNTs as is evident in Fig.…”
Section: 373mentioning
confidence: 99%
“…418 Doping strategies have been attempted by many groups to achieve higher carrier concentrations and thus lower R s values in graphene. Following early reports on CNTs, 381,382 doping of graphene has been achieved through chemical treatments with nitric acid and gold chloride. 329,[419][420][421][422] However, even these doped CVD graphene anode devices fail to surpass the performance of control ITO anode devices.…”
Section: Graphene In Photovoltaicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our homes or offices, they are found in flat panel displays such as in TVs, laptops and in touch panels, of phones, tablet computers, E-readers and digital cameras [1]. Besides, they are also used as the electrodes for photovotaic devices such as solar cells [2] and organic light-emitting diodes (OLEDs) [3]. Liquid crystal display (LCD) is by far the largest user of transparent conductive films but many devices are showing rapid growth in popularity such as touch panels (362 million units in 2010 with annual growth of 20% through 2013), E-paper (30 fold growth expected from 2008 to 2014), and thin film solar cells (expected sales of over $13 billion by 2017) [4].…”
Section: Introductionmentioning
confidence: 99%